2015
DOI: 10.1021/nl504941q
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Line Width Narrowing and Spectral Jumps of Single Stable Defect Centers in ZnO at Cryogenic Temperature

Abstract: Finding new solid state defect centers in novel host materials is crucial for realizing integrated hybrid quantum photonic devices. We present a preparation method for defect centers with photostable bright single photon emission in zinc oxide, a material with promising properties in terms of processability, availability, and applications. A detailed optical study reveals a complex dynamic of intensity fluctuations at room temperature. Measurements at cryogenic temperatures show very sharp (<60 GHz) zero phono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 36 publications
4
49
1
Order By: Relevance
“…The abrupt leading edge was due to a 570 nm long-pass filter. The emission range matches the previous reports by Morfa et al [22], Choi et al [23,24], and Neitzke et al [26], where their single defects also showed broad red fluorescence. In this study, the results reveal that ZnO optical defects have distinct and resolvable emission peaks compared to the aforementioned work at room temperature.…”
Section: Optical Characterisation Of Zno Nps On Top Of Silica Substratesupporting
confidence: 91%
See 2 more Smart Citations
“…The abrupt leading edge was due to a 570 nm long-pass filter. The emission range matches the previous reports by Morfa et al [22], Choi et al [23,24], and Neitzke et al [26], where their single defects also showed broad red fluorescence. In this study, the results reveal that ZnO optical defects have distinct and resolvable emission peaks compared to the aforementioned work at room temperature.…”
Section: Optical Characterisation Of Zno Nps On Top Of Silica Substratesupporting
confidence: 91%
“…In this study, the results reveal that ZnO optical defects have distinct and resolvable emission peaks compared to the aforementioned work at room temperature. It must be noted that Neitzke et al [26] also observed a very narrow zero phonon line at 580 nm when they measured their ZnO optical defects at cryogenic temperatures, which greatly suppresses their phonon sideband emission from 600 to 750 nm.…”
Section: Optical Characterisation Of Zno Nps On Top Of Silica Substratementioning
confidence: 99%
See 1 more Smart Citation
“…Other groups found the singlephoton emission ranging from around 1.55 to 2.21 eV. Jungwirth et al measured 19 different defects in ZnO [10] and about 30 defect center locations have been investigated by Neitzke et al [51]. They obtained antibunching curves with similar spectral range.…”
Section: Single-photon Sources (Spss) From Znomentioning
confidence: 91%
“…For clear understanding of the ZnO defects, low temperature PL measurement was performed by Neitzke et al [51]. Sixteen defects from the same ZnO sample were investigated at 5 K and Figure 4 shows one of the PL spectra of the defects consisting of the shape of ZPL and a phonon sideband.…”
Section: Single-photon Sources (Spss) From Znomentioning
confidence: 99%